Complete Nucleotide Sequences of mcr-4.3-Carrying Plasmids in Acinetobacter baumannii Sequence Type 345 of Human and Food Origin from the Czech Republic, the First Case in Europe - Bitar, Ibrahim; Medvecky, Matej; Gelbicova, Tereza; Jakubu, Vladislav; Hrabak, Jaroslav; Zemlickova, Helena; Karpiskova, Renata; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2019)
Here, we describe two plasmids carrying mcr-4.3 in two Acinetobacter baumannii strains isolated from imported food and a clinical sample. The comparative analysis of these plasmids, with two other plasmids reported in the NCBI database, highlighted the common origin of the plasmidic structure carrying mcr-4.3 This is the first case of the mcr-4.3 gene in a A. baumannii strain isolated from a clinical case in Europe. We hypothesize that food import is initiating the spread in Czech Republic.
Keywords: Plasmids; Česká republika; Drug Resistance, Bacterial; Microbial Sensitivity Tests; Europe; Acinetobacter baumannii; Czech Republic; Evropa; senioři nad 80 let; lidé; ženské pohlaví; Humans; bakteriální léková rezistence; mikrobiální testy citlivosti; plazmidy; Aged, 80 and over; Peptides; peptidy; Female